Hipertensión y su relación con el sodio, el potasio, el calcio y el magnesio (2006)
Hypertension is a major risk factor for many cardiovascular diseases including stroke, coronary heart disease, cardiac failure, and end stage renal disease. Elevated blood pressure results from interactions between environmental, nutritional and genetic factors. A wide scientific evidence strongly supports the concept, that nutritional components can affect the blood pressure. There are some comprehensive lifestyle and dietary modifications that can substantially lower blood pressure and improve blood pressure control. African-Americans particularly are more sensible to reduce blood pressure when they decrease salt consumption, reduced intake of alcohol, increase potassium intake and follow the DASH Diet. Elderly people, with high blood pressure are at risk for chronic disease and they can also get beneficial effects of healthful lifestyle modifications in the prevention and management of hypertension. Some epidemiologic and clinical trials with animal models have assessed the relationship between increased dietary calcium intake and its protective role for the control of hypertension, therefore scientific studies to prove these facts are still going on and more scientific evidence is necessary.